Retrospective Study of Salinomycin Toxicosis in 66 Cats - Akos Pakozdy; Iris Challande-Kathman; Marcus Doherr; Sigitas Cizinauskas; Simon J. Wheeler; Anna Oevermann; Andre Jaggy (Veterinary Medicine International)
We examined 66 cats with salinomycin intoxication. Salinomycin caused different LMN signs of varying degrees of severity in all cases. Changes in blood work were unspecific, with the most frequent being increased serum creatine kinase activity, leukocytosis, and increased liver enzymes. Pathological electrodiagnostic findings: fibrillation potentials and positive sharp waves were detected in 10 cases, motor nerve conductance velocity was mildly decreased in 8/12 cats, and sensory nerve conductance velocity and repetitive nerve stimulation were normal in all examined cases. In five cases the peripheral neuropathy was confirmed by pathohistology. Fluid therapy and supportive care were used as therapy and 52 cats recovered completely. The probability for complete remission was significantly different between mildly and severely affected cases. It seems that the severity of clinical signs and prognosis correlate well with the amount of toxin ingested. We conclude that early recognition and decontamination combined with supportive care results in complete recovery.